1744. Association Between Antibiotic Prescribing for Urinary Tract Infection (UTI) and UTI Severity of Illness Upon Admission to Hospitals in New York State. (15th December 2022) - Nero, Alexa; Weber, Mckayla; Carreno, Joseph
Abstract: Background: It has been previously demonstrated that county-level antibiotic prescribing (CP) and resistance (AR) influence urinary tract infection (UTI) severity of illness upon hospital presentation in New York State (NYS, Grillo et al. IDWEEK 2021). However, previous investigations were geographically limited to the most densely populated regions of NYS. This study builds on the previous study by evaluating additional NYS regions and outcomes. Methods: Retrospective, cross-sectional study, combining data from NYS Statewide Planning and Research Cooperative System (SPARCS) and previously published data on CP for UTI in female Medicare beneficiaries. Eligibility criteria: female patients admitted to a NYS inpatient setting in 2017, UTI (CCS 159), Medicare insurance. New York county (Manhattan) county was excluded. CP was the primary exposure. "Low" or "high" CP was based on the statewide median. Severe infection (All-patient refined severity of illness on admission ≥ 3, SI) was the primary outcome. Association between CP and SI, hospitalization costs, were evaluated using chi-square, logistic regression, Mann-Whitney U test. Log-rank test assessed time to discharge, censoring those that went to hospice or died inpatient. Results: 13, 173 patients were included, 4, 250 (32.3%) low CP, 8, 923 (67.7%) high CP. Baseline demographics (Figure 1) that differed between groups included age, race, ethnicity, and emergency admission (P < 0.001, χ 2 test). In the multivariable logistic regression analysis low CP was associated with increased odds for severe urinary tract infection after adjusting for potential confounders (aOR: 1.08 [1.003 – 1.163]). Additional factors associated with severe infection are presented in Figure 2. Median (IQR) hospital costs were similar but statistically significantly lower in the low CP group (Figure 3), median (IQR) time to hospital discharge was 4 days in each group (P < 0.001). Figure 1. Adjusted Odds Ratios for Severe Urinary Tract Infection Figure 2. Hospital Costs Conclusion: Low CP may be a risk factor for severe initial presentation to the hospital in UTI. Further research is needed to examine the effects of prescribing patterns and additional factors that may influence severity of infection in this setting. Disclosures: Joseph Carreno, PharmD, MPH, Accelerate Diagnostics: Advisor/Consultant|IDbyDNA: Advisor/Consultant.